Synthesis of cobalt oxide-manganese oxide on activated carbon electrodes for electrochemical capacitor application using a liquid phase plasma method. (18th May 2016) - Lee, Heon; Kim, Byung-Hoon; Park, Young-Kwon; An, Kay-Hyeok; Choi, Yun-Ju; Jung, Sang-Chul
Abstract: An Electrochemical capacitor electrode material was prepared by precipitating cobalt-manganese oxide nanoparticles on the surface of activated carbon powder (ACP) using a liquid phase plasma method. Polycrystalline spherical 100–170 nm-sized metal oxide nanoparticles were precipitated onto the ACP surface with a high degree of uniformity. The initial concentration of precursor influenced the composition of the precipitated nanoparticles. The nanoparticles were bimetallic oxide nanoparticles composed mainly of Co 2+ and Mn 3+ . Increases in the amount of metal oxide nanoparticles precipitated on ACP, were accompanied by reduced specific surface area, average pore size, and total pore volume, as well as by increased specific capacitance. The metal oxide nanoparticles improved the cyclic stability of the electrochemical capacitor and reduced equivalent series resistance. Graphical abstract: Electrochemical capacitor electrode was generated by precipitating cobalt-manganese oxide nanoparticles on the surface of activated carbon powder (ACP) using a liquid phase plasma method. Polycrystalline structure of spherical 100–170 nm-sized metal oxide nanoparticles was precipitated very uniformly on the ACP surface. The nanoparticles were bimetallic oxide nanoparticles composed mainly of Co 2+ and Mn 3+ . Highlights: Liquid phase plasma process was used to synthesize cobalt-manganese oxide/carbon composite. Uniform dispersion of spherical metal oxide nanoparticles on the carbon surface. The initial concentration of precursor influenced the composition of the nanoparticles precipitated. The nanoparticles were bimetallic oxide nanoparticles composed mainly of Co 2+ and Mn 3+ . The metal oxide nanoparticles improved the cyclic stablilty and reduced equivalent series resistance.